«QARAQALPAQSTAN» RADIOKANALI INTERVYULERINIǸ TEMATIKASI (Konferensiyalar | Conferences, 2023)
The article was about the topic of radio channel interviews "Karakalpakstan". The journalist is studied at the time of radiointerview broadcast.